PILOT STUDY OF AN ANALYSIS OF MOTOR SKILLS INHERENT TO SLAP SHOT (Fiep Bulletin - online, 2015)
INTRODUCTION: In Brazil, the Olympic Winter sports practice is very scarce due primarily to weather conditions. However in winter Olympic Edition based in Sochi, in Russia, the Brazil attended by twenty athletes, the biggest number of athletes sent by Brazil to this competition so far and also participated in the first Pan American Ice hockey with only one naturalized athlete. This shows that the practice of these sports, by Brazilians, is increasing. The present study is characterized by a pilot study and aimed to check whether the Shuttle Run test and Flegner Power Test are effective tests to check motor skills inherent in slap shot, kick more powerful than ice hockey. The study is justified by the shortage produced in Brazil about this literary theme. MATERIAL AND METHODS: The sample included three Brazilian athletes who participated in the first Pan American Ice hockey and who were singled out by coach of the Brazilian men's national ice hockey team as athletes who best perform the slap shot. As an instrument of data collection were used the Flegner Power Test and the Shuttle Run test. Data collection was carried out on a date with each athlete and they were subjected to the tests on different days, but in the same place and the same time of the day. RESULTS: in the Shuttle Run test the average time was 10:10 seconds and Flegner Power Test the average absolute anaerobic power unit (AAPU) amounted to 254.07 and all tested showed a predominance of slow fibers. CONCLUSION: The tests used may not be the best way to verify motor skills in question in ice hockey. The main limiter of the tests was the difference in terrain where they were carried out the tests and the land on which it is practiced the sport.
Keywords: Motor Skill; Slap Shot; Flegner Power Test.